2002
DOI: 10.1103/physrevb.66.075424
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport in a quasi-one-dimensional channel on suspended helium films

Abstract: Quasi-one dimensional electron systems have been created using a suspended helium film on a structured substrate. The electron mobility along the channel is calculated by taking into account the essential scattering processes of electrons by helium atoms in the vapor phase, ripplons, and surface defects of the film substrate. It is shown that the last scattering mechanism may dominate the electron mobility in the low temperature limit changing drastically the temperature dependence of the mobility in compariso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The electron transport in quasi-one-dimensional channels on the liquid helium surface at presence of inhomogeneities on a substrate was considered in Ref. 9. It has been shown that the mobility of carriers limited by scattering of electrons by defects, can be presented as…”
Section: Discussionmentioning
confidence: 99%
“…The electron transport in quasi-one-dimensional channels on the liquid helium surface at presence of inhomogeneities on a substrate was considered in Ref. 9. It has been shown that the mobility of carriers limited by scattering of electrons by defects, can be presented as…”
Section: Discussionmentioning
confidence: 99%
“…8 Because the electron does not adiabatically follow the profile of the interface film substrate and the electron-roughness interface scattering potential is independent of the electron wave function we use the same wave function in both scattering mechanisms. 17 To a good approximation Ĥ er(ei) can be expanded in 1 keeping the first-order term. This term is linear in (1,2) (r)ϭ ͚ q (1,2)q e iq•r ,…”
Section: U͑z ͒ϭϫmentioning
confidence: 99%
“…One should say that the study of the properties of SE's over a helium film is indeed a difficult experimental task due to the influence of substrate inhomogeneities which produce other scattering processes due to interface roughness, 16 static charges trapped by defects, suppression of the film thickness due to the electrostatic pressure, and others. Furthermore the electron-ripplon scattering itself is modified considerably in comparison with the bulk case.…”
Section: Introductionmentioning
confidence: 99%